Tax Avoidance Dan Kepemilikan Institusional Terhadap Audit Delay Pada Perusahaan Sub-Sektor Minyak Dan Gas - Ainun Rohmah; Atalia Meisya P.; Dwi Sri Wahyuni; Nabila Dwi S.; Dwi Ermayanti S. (LPPM POLITEKNIK LP3I BANDUNG, 2024)
There are still many delays in submitting financial reports to companies, this delay can have a negative impact on the company. In this study, the researchers re-examined the factors affecting the delay in financial reporting, taking into account other factors, namely tax evasion and institutional ownership. The purpose of this study was to determine the effect of tax avoidance and institutional ownership on audit delay in oil and gas sub-sector companies. The method used in this research is quantitative using SPSS software. This research uses secondary data in the form of financial reports on the IDX with the object of research being oil and gas sub-sector companies with the period 2019 to 2021. financial reports, taking into account other factors, namely tax evasion and institutional ownership. financial statements, taking into account other factors, namely tax evasion and institutional ownership. The results of the study using the partial test (t test) show that the results of tax avoidance (X1) have significant results on audit delay, but institutional ownership (X2) has insignificant results on audit delay (Y). Based on the simultaneous test (f test) the tax avoidance variable (X1) and institutional ownership (X2) have a significant influence on audit delay (Y) in coal sub-sector companies in 2019-2021.